Integrated business processes with ERP systems - Magal, Simha; Word, Jeffrey (Hoboken, NJ : Wiley, 2012)
Written in partnership with SAP,'Integrated Business Processes with ERP Systems' covers all of the key processes supported by modern ERP systems. This text approaches the topics using an integrated process perspective of the firm and includes a detailed case study that is used throughout the text to illustrate concepts.
'Written with the support of SAP'--Cover.
Includes bibliographical references and index.
Keywords: SAP ERP -- Textbooks; Business planning -- Computer programs -- Textbooks; Business enterprises -- Computer programs -- Textbooks; Integrated software -- Textbooks